1983
DOI: 10.1007/bf01990088
|View full text |Cite
|
Sign up to set email alerts
|

Hypergravity promotes cell proliferation

Abstract: When HeLa cells, chicken embryo fibroblasts, sarcoma Galliera cells, Friend leukemia virus transformed cells and human lymphocytes are cultured in a hypergravitational field (e.g. 10 X g) proliferation rate is increased by 20-30%, whereas glucose consumption per cell is lower than at 1 X g. Tracking of cell movements on gold-coated substrates reveals that cell migration is hindered at high-g. These findings suggest that under gravitational stress the cell is either capable of shifting to other metabolic pathwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0

Year Published

1992
1992
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(21 citation statements)
references
References 19 publications
0
21
0
Order By: Relevance
“…Centrifugation of cells to study stress response in cell differentiation has a long history dating back to the early 20th century (9,33). The method was later applied to research in virology, presumably for directly depositing viral particles on cells to enhance infection (13).…”
mentioning
confidence: 99%
“…Centrifugation of cells to study stress response in cell differentiation has a long history dating back to the early 20th century (9,33). The method was later applied to research in virology, presumably for directly depositing viral particles on cells to enhance infection (13).…”
mentioning
confidence: 99%
“…Hypergravity stimulates proliferation of various types of human cells (6,7), presumably by enhancing the expression of early response genes such as c-myc (8,10) and activating processes involved in cell cycle progression such as phosphorylation (9). Studies of hypergravity are needed as a counterpart to those aimed at determining the influence of micro-gravity, urgently required for the near-future residents of the International Space Station.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the micro-gravity experienced in space flight is known to suppress the epidermal growth factor (EGF)-dependent gene expression of c-fos and c-jun (1,2), phorbor ester-induced T cell activation (3), gene expression in osteoblasts (4), and self-organization of microtubules (5). Hypergravity, in contrast, has been reported to promote the proliferation of several cell lines in culture (6), mitogenic responses of human lymphocytes (7), gene expression of c-myc (8), production of inositol 1,4,5-triphosphate (9), phosphorylation of microtubule-associated protein (MAP) (9), and early response gene expression in osteoblasts (10). The objectives of most of the studies have been mainly to elucidate the effects of microgravity on human bodies in space, especially in the International Space Station, currently under construction.…”
mentioning
confidence: 97%
“…Similarly, protein synthesis was normal after 80 min of centrifugation at 50,000 x g. Tschopp and Cogoli (300) subjected five different cells (HeLa cells, chicken embryo fibroblasts, rat sarcoma cells, Friend leukemia virus-transformed cells, and human lymphocytes) to centrifugation at 10 to 40 x g for up to 4 days and found that cell proliferation was enhanced. Of the five cells studied, only lymphocytes did not survive a 3-day exposure to centrifugation greater than 20 x g. The increase in cell proliferation was due to the g effect and not to an increase in hydrostatic pressure generated by centrifugation.…”
Section: Centrifugation Of Cellsmentioning
confidence: 99%